Patient-derived orthotopic xenograft models of medulloblastoma lack a functional blood-brain barrier. Issue 5 (1st December 2020) - Genovesi, Laura A; Puttick, Simon; Millar, Amanda; Kojic, Marija; Ji, Pengxiang; Lagendijk, Anne K; Brighi, Caterina; Bonder, Claudine S; Adolphe, Christelle; Wainwright, Brandon J
Abstract: Background: Novel targeted therapies for children diagnosed with medulloblastoma (MB), the most common malignant pediatric brain tumor, are urgently required. A major hurdle in the development of effective therapies is the impaired delivery of systemic therapies to tumor cells due to a specialized endothelial blood-brain barrier (BBB). Accordingly, the integrity of the BBB is an essential consideration in any preclinical model used for assessing novel therapeutics. This study sought to assess the functional integrity of the BBB in several preclinical mouse models of MB. Methods: Dynamic contrast enhancement magnetic resonance imaging (MRI) was used to evaluate blood-brain-tumor barrier (BBTB) permeability in a murine genetically engineered mouse model (GEMM) of Sonic Hedgehog (SHH) MB, patient-derived orthotopic xenograft models of MB (SHH and Gp3), and orthotopic transplantation of GEMM tumor cells, enabling a comparison of the direct effects of transplantation on the integrity of the BBTB. Immunofluorescence analysis was performed to compare the structural and subcellular features of tumor-associated vasculature in all models. Results: Contrast enhancement was observed in all transplantation models of MB. No contrast enhancement was observed in the GEMM despite significant tumor burden. Cellular analysis of BBTB integrity revealed aberrancies in all transplantation models, correlating to the varying levels of BBTB permeability observed by MRI in these models. Conclusions: These results highlight functional differences in the integrity of the BBTB and tumor vessel phenotype between commonly utilized preclinical models of MB, with important implications for the preclinical evaluation of novel therapeutic agents for MB.